1981
DOI: 10.1086/159374
|View full text |Cite
|
Sign up to set email alerts
|

The cool half of the H-R diagram in soft X-rays

Abstract: We report results of an Einstein Guest Observing program to map the occurrence of soft X-ray emission, which is a signature of hot stellar coronae (T > 10 6 K), in the cool half of the Hertzsprung Russell (H-R) diagram. We detect X-rays from F-M dwarfs and late F through early K giants, but not from the cooler giants, other than the spectroscopic binary e Car (KO II + B), or from any supergiants, other than Canopus (F0 Ib-II). The empirical separation of the cool half of the H-R diagram into a region where ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0
2

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(68 citation statements)
references
References 4 publications
2
64
0
2
Order By: Relevance
“…Ayres et al (1981) attempted to observe soft X-ray emission from late-type stars, being a signature of stellar coronae (T > 10 6 K). They found an "X-ray DL" roughly coinciding with the "transition region DL" from Linsky & Haisch (1979); only stars to the blue side were detected in X-rays.…”
Section: Coronal Transition Region and Wind Dividing Linesmentioning
confidence: 99%
“…Ayres et al (1981) attempted to observe soft X-ray emission from late-type stars, being a signature of stellar coronae (T > 10 6 K). They found an "X-ray DL" roughly coinciding with the "transition region DL" from Linsky & Haisch (1979); only stars to the blue side were detected in X-rays.…”
Section: Coronal Transition Region and Wind Dividing Linesmentioning
confidence: 99%
“…The concept of dividing lines (DL) was introduced on the basis of early FUV observations by Linsky & Haisch (1979) and of soft X-ray observations by Ayres et al (1981) with the IUE and the Einstein observatory, respectively. These authors found a sharp division around mid K spectral type: hotter giants exhibit solar-like activity signatures with hot (10 5 −10 6 K) gas indicating the existence of chromospheres, transition regions and coronae, while cooler giants only show chromospheric temperatures around 10 4 K. Earlier, Reimers (1977) had found strong, cool outflows in giants cooler than mid K spectral type, which suggests a transition from hot coronae to massive, cool winds as a star crosses the DL region in the course of stellar evolution.…”
Section: Introductionmentioning
confidence: 99%
“…1) showed evidence of neither ultraviolet ( UV ) radiation of C iv (T $ 10 5 K; Linsky & Haisch 1979) nor soft X-ray (T $ 10 6 K; Ayres et al 1981). Stencel & Mullan (1980) further pointed out that the stellar winds appear cool and massive after stars cross the DL.…”
mentioning
confidence: 99%